2010
DOI: 10.1186/1743-7075-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training in overweight women on a ketogenic diet conserved lean body mass while reducing body fat

Abstract: BackgroundThe aim of the present study was to compare the effects of 10 weeks resistance training in combination with either a regular diet (Ex) or a low carbohydrate, ketogenic diet (Lc+Ex) in overweight women on body weight and body composition.Methods18 untrained women between 20 and 40 years with BMI ≥ 25 kg*m-2 were randomly assigned into the Ex or Lc+Ex group. Both groups performed 60-100 min of varied resistance exercise twice weekly. Dietary estimates were based on two 4-day weighed records. Body compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 75 publications
3
41
0
2
Order By: Relevance
“…It is a form of dietary pattern that has been subject to intense scrutiny especially across the decades since the popularization of the Atkins diet and, apart from its positive effects on weight loss, the shortterm use of energy-sufficient KD has not been associated with any long-term health issues; the few symptoms such as fatigue and headaches disappear after a few days (22). Biochemical, physiological, and observational studies also provide good evidence that an actual KD (i.e., where adherence is checked) can lead to fat loss with little or no loss of muscle mass (13,25). Indeed, it is a common misconception that the KD intuitively is unsafe because it is a ''high-protein, highYsaturated fat'' diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is a form of dietary pattern that has been subject to intense scrutiny especially across the decades since the popularization of the Atkins diet and, apart from its positive effects on weight loss, the shortterm use of energy-sufficient KD has not been associated with any long-term health issues; the few symptoms such as fatigue and headaches disappear after a few days (22). Biochemical, physiological, and observational studies also provide good evidence that an actual KD (i.e., where adherence is checked) can lead to fat loss with little or no loss of muscle mass (13,25). Indeed, it is a common misconception that the KD intuitively is unsafe because it is a ''high-protein, highYsaturated fat'' diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that resistance training can increase muscle mass and help mitigate loss of fat-free mass during weight loss (Ballor et al 1988;Delmonico & Lofgren, 2010;Stiegler & Cunliffe, 2006). Only two studies were located that have investigated whether combining resistance training with a ketogenic diet provides superior changes in body composition relative to other diets in combination with resistance training (Jabekk et al, 2010;Wood et al, 2012).…”
Section: Resistance Training and Ketogenic Dietsmentioning
confidence: 99%
“…As detailed in Table 2, these studies were markedly different on a number of factors, including subject age and gender, frequency of strength training, exercise selection, sets and repetitions performed, and method of body composition assessment. Jabekk et al (2010) reported no change in fat-free mass in subjects following a resistance training program in combination with a ketogenic diet, and Wood et al (2012) reported a decrease. However, the results from Wood et al (2012) indicated that, without exercise, a ketogenic diet led to less fat-free mass loss than a low-fat diet and similar losses as compared to a low-fat diet plus resistance training.…”
Section: Resistance Training and Ketogenic Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in overweight women suggested that a LCHF diet in combination with resistance training reduced body weight and fat mass while maintaining lean body mass, whereas resistance training in combination with a regular higher-carbohydrate diet increased fat-free mass but maintained fat mass (Jabekk et al, 2010). These changes are at least partially due to reduced anti-lipolytic insulin action and protein-protective action of increased total and free thyroxine index after a LCHF diet (Volek et al, 2002).…”
Section: Lchf Diet and Body Compositionmentioning
confidence: 99%